Information retrieval technology : (Springer, 2006)
This book constitutes the refereed proceedings of the Third Asia Information Retrieval Symposium, AIRS 2006, held in Singapore in October 2006. The content of the book address all current issues in information retrieval including applications, systems, technologies and theoretical aspects of information retrieval in text, audio, image, video and multi-media data.